The state of the antioxidant system in young sheep with trace element diseases - N. M. Fedorovych; L. G. Slivinska (Ukrainian Journal of Veterinary and Agricultural Sciences)
Microelements are essential for the normal functioning of the body's antioxidant system. Their deficiency causes disruptions in the functioning of enzymatic and non-enzymatic antioxidant systems, leading to oxidative stress. This study aimed to investigate the impact of Cobalt, Copper, Zinc, and Iron deficiency on the antioxidant system status in the bodies of Precoce breed lambs. The study was conducted at the NEPC “Komarnivske” in the Horodok district of the Lviv region on lambs aged 3–5 months. 60 % of the lambs had satisfactory body condition, medium body structure, compact constitution, dull wool, dry skin with reduced elasticity, 80 % exhibited hypothermia, and 35 % had anemic visible mucous membranes, moderately moist, intact, without layering or swelling. Upon auscultation, 20 % of the lambs showed weakened fist and second heart tones, and 10 % exhibited splitting and doubling of these tones. Reduced appetite and distorted taste were noted, manifested by bedding consumption. Blood analysis of sick animals revealed deficiencies of Cobalt (28.3 %; P < 0.001), Copper (33.4 %; P < 0.001), Zinc (27.3 %; P < 0.01), and Iron (16.1 %; P < 0.001), an increase in lipid hydroperoxides by 37.7 % (P < 0.001), TBK-active products by 17.0 % (P < 0.001), a decrease in glutathione peroxidase activity by 21.7 % (P < 0.001), glutathione reductase by 20.6 % (P < 0.001), superoxide dismutase by 37.1 % (P < 0.001), and catalase by 22.4 % (P < 0.001) compared to clinically healthy animals. A positive correlation was established between the content of Copper and TBK-active products (r= +0.334), Cobalt and TBK-active products (r= +0.543), Cobalt and glutathione peroxidase activity (r= +0.302), Cobalt and catalase activity (r=+ 0.350), Zinc and reduced glutathione (r= +0.488). Therefore, in lambs with microelement deficiencies, oxidative stress occurs with significant differences in antioxidant status, as reflected in the evaluation of certain enzymatic and non-enzymatic antioxidants between clinically healthy and microelement-deficient lambs. Serum activity of superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase, lipid hydroperoxide levels, TBK-active products, and reduced glutathione may serve as diagnostic indicators of antioxidant status in sheep with microelement deficiencies.